On the question of the «right to anonymity» on the Internet (International relations and international law Journal, 2018)
The purpose of this article is to describe the main features of the legal regulation of anonymous activity on social networks in the Republic of Kazakhstan and to highlight the most common legal problems. The authors emphasize that the right to anonymity on the Internet is not absolute, and is not an integral part of the right to freedom of expression and free receiving and dissemination of information. In particular, special attention is paid to the legal relationships arising between the owners of the Internet – resources and the users posting comments. The article provides a detailed analysis of the legislation regulating the right to anonymous activity of the users of the Internet, as the media. Thus, the authors propose specific amendments to existing information legislation.Key words: Internet resource, information, legal regulation, social networks, the right to anonymity, personal data.